(untitled) (Italian Journal of Public Health, 2007)
Background: For the last 20 years, Sweden has changed from a homogeneous to multicultural society with about 20% of immigrants born in other countries. The existing Swedish studies have not shown coherent results on how access to health care services varies by ethnicity. The aim of this paper was to analyze the association between country of birth and refraining from seeking medical treatment and whether socioeconomic disadvantage modifies this association. Methods: Cross-sectional Swedish National Survey of Public Health 2004. A population-based sample comprising of 14,732 men (1,382 immigrants) and 17,115 women (1,717 immigrants) aged 21 to 84 years. Country of birth was categorised as being born in Sweden, other OECD countries or other countries (non- OECD). The main outcome was the self-reporting of refraining from seeking medical treatment during the past three months. Data was collected within a three-month period during the spring of 2004 and was based on a postal self-administered questionnaire linked to registry data from Statistics Sweden. The nonresponse rate was 37%. Main results: In spite of the fact that immigrants reported poorer health status, they were more likely to refrain from seeking medical treatment as compared to Swedish-born residents (odds for immigrants from other OECD countries were ORmen = 2.2, 95% CI 1.8-2.6 and ORwomen = 1.8, 95% CI 1.5-2.1 and for immigrants from other countries (ORmen = 3.1, 95% CI 2.4-3.4 and ORwomen = 2.3, 95% CI 1.8-2.9). Socioeconomic disadvantage (SDI) did not explain why immigrants fromother OECD countries had increased odds for refraining fromseekingmedical treatment. However SDI explained about 20%of the increased odds for refraining from seeking medical treatment among immigrants from other (non-OECD) countries. Conclusions: Socioeconomic disadvantage does not fully explain why immigrants refrain from seeking medical treatment. Public health strategies towards the goal “care on equal terms” cannot be achieved without addressing wider socioeconomic determinants including interactions between class and ethnicity.